Effects of butylated hydroxytoluene on protein P25b, chilled and cryopreserved bull semen in Bioxcell®, tris- and citrate-egg yolk extenders - Mada, Khumran Armiya'u (2016)
Semen quality drops after cryopreservation, which is caused by high oxidative stress exerts on the sperm during freezing and thawing procedures. The consequenceof this effect is that the protein composition of the spermatozoa especially P25b is adversely affected, thereby hindering the protein‟s role in fertilization. The sperm surface P25b is considered a bull fertility marker, very important in zona pellucida binding during fertilization. Thus, the fertility of spermatozoa may be preserved if P25b is protected. The aim of this study is to investigate the effects of various concentrations of antioxidant butylated hydroxytoluene (BHT) in three semen extenders with the view to preserving the spermatozoa quality and protecting the P25b from damage during chilling as well as cryopreservation. Four bulls were initially selected and their ejaculates were assessedfor color, volume, concentration, pH, general and progressive motilities, morphologically normal spermatozoa, acrosome and DNA damage, and lipid peroxidation. Transmission electron microscopy (TEM) was also performed to evaluate the ultrastructures of the spermatozoa.The assessment revealedthat the semen color varied from creamy-white in bull #1, to milky white in bulls #2 and 4, then cloudy in bull #3. Highest sperm concentration, lipid peroxidation and pH were recorded from bull #4. Highest volume, progressive motility, morphology, less acrosome damage and viability were from bull #2. While best values for general motility and DNA damage were obtained from bull #1. TEMrevealed 92.5, 90.0 and 82.5 percent of intact heads for bulls #1, 2 and 3, respectively, significantly higher than bull # 4 (62.5%). In addition, TEM also showed 32.5, 25.0, and 37.5% of total defective spermatozoa in the respective bulls #1, 2 and 3, significantly lower than 80.0% in bull # 4. Bulls #1, 2 and 3 were therefore consistently satisfactory in most parameters evaluated and hence considered havinghigh semen freezability potential. On the other hand, bull #4 expressed higher (p < 0.05) sperm concentration but yet unsatisfactory in most other parameters assessed, including the low live/dead ratio and high percentage of abnormalities, manifesting poor potential of freezability.The three bulls with high semen freezability potential were then usedfor the study. Semen samples were collected by electroejaculation, diluted with Bioxcell®, tris- or citrate- egg yolk extenders supplemented with 0.0 (control), 0.5, 1.0, 1.5, 2.0 and 3.0 mM/mL concentrations of BHT. Thereafter, the dilutedsamples were either chilled at 4oC for three days or frozen at -196oC in liquid Nitrogen for 14 days. At the end of storage time, four straws were randomly pooled from each group and evaluated. Results showed that addition of BHT at 0.5 mM/mL in Bioxcell®, 1.0 mM/mL in tris- and 1.0 to 1.5 mM/mL in citrate egg yolk extenders have improved (p<0.05) spermatozoa morphology, viability and protection against acrosomal damage when compared with the control after chilling. After cryopreservation, general motility, progressive motility, morphology, protection against acrosomal damage, DNA damage and lipid peroxidation (LP) of the spermatozoa were significantly improved compared with the control at the same BHT concentrations as in the chilledsamples for the various extenders. The appropriate BHT concentration in each extender as demonstrated in the chilling and freezing were also consistent in the protection of P25b (p<0.05) than in the control after SDS-PAGE gel densitometry. The spermatozoa quality parameters assessed in both the chilling and freezing samples deteriorated (p<0.05) against control at higher BHT concentrations of 2.0 and 3.0 mM/mL in all the extenders. However, the deterioration of the concentration of P25b at 2.0 and 3.0 mM/mL BHT were the same as the control in all the extenders. The outcome of this study strongly suggests a better bull sperm fertility potential after BHT supplementationof 0.5 mM/mL in Bioxcell®, 1.0 mM/mL in tris- egg yolk and 1.0 to 1.5 mM/mL in citrate- egg yolk extenders.